Altered mental status caused by hypertriglyceridemia in an adolescent - I. C. Olakunle; J. D. Tobias (Pediatric Anesthesia and Critical Care Journal (PACCJ))
A long list of diseases and disorders can result in altered mental status in pediatric-aged patients including neurologic, infectious, toxicological, traumatic, metabolic, and psychiatric etiologies. Laboratory testing and radiologic imaging is frequently necessary to further narrow the differential diagnosis. We present a 13-year-old adolescent who presented with altered mental status that was originally attributed to metabolic derangements associated with diabetic ketoacidosis. The subsequent laboratory work-up demonstrated lipemic serum with profound hypertriglyceridemia, which was eventually thought to be the etiology of his altered mental status. As treatment resulted in correction of the hypertriglyceridemia, his mental status improved and returned to baseline. The pathophysiology of lipid metabolism is reviewed, etiology of hypertriglyceridemia presented, and mechanisms for its role in altered mental status discussed.